2021
DOI: 10.36076/ppj.2021.24.e453
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Carpal Injection of Ozone versus Methylprednisolone in Carpal Tunnel Syndrome of Systemic Sclerosis Patients: A Randomized Single-Blind Clinical Trial

Abstract: BACKGROUND: Carpal tunnel syndrome (CTS) is the most entrapment syndrome in general and is the most frequent peripheral nervous system involvement in systemic sclerosis (SSc). Local injection of steroid hydrodissection or ozone-oxygen showed favourable outcome in CTS in general. OBJECTIVES: To compare the clinical efficacy of ozone versus methylprednisolone intracarpal injection upon pain, functional status, and nerve conduction in patients with CTS due to SSc. STUDY DESIGN: A randomized single-blinded trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Carpal tunnel syndrome (CTS) is one of the most common entrapment disorders in general and the most recurring peripheral nervous system involvement in SSc [ 130 , 131 ]. Elawamy et al demonstrated that both intracarpal ozone or methylprednisolone reported advantageous impacts upon CTS in people with SSC; nonetheless, ozone relieves pain, enhances the hand functioning, decreases the duration and frequency of Raynaud’s attacks, declines the size of ulceration, and improves median nerve conduction study over the 6-month follow-up [ 132 ]. Rascaroli et al found slight improvements in sensory and motor parameters after ozone therapy, and Bahrami et al showed improvement of median sensory nerve action potential latency, compared to the pre-treatment level in both groups (one group treated with wrist volar splint alone, the other group treated with ozone injection and splint) [ 133 , 134 , 135 , 136 ].…”
Section: Oxygen-ozone and Rheumatic Diseasesmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is one of the most common entrapment disorders in general and the most recurring peripheral nervous system involvement in SSc [ 130 , 131 ]. Elawamy et al demonstrated that both intracarpal ozone or methylprednisolone reported advantageous impacts upon CTS in people with SSC; nonetheless, ozone relieves pain, enhances the hand functioning, decreases the duration and frequency of Raynaud’s attacks, declines the size of ulceration, and improves median nerve conduction study over the 6-month follow-up [ 132 ]. Rascaroli et al found slight improvements in sensory and motor parameters after ozone therapy, and Bahrami et al showed improvement of median sensory nerve action potential latency, compared to the pre-treatment level in both groups (one group treated with wrist volar splint alone, the other group treated with ozone injection and splint) [ 133 , 134 , 135 , 136 ].…”
Section: Oxygen-ozone and Rheumatic Diseasesmentioning
confidence: 99%
“…[ 19 ] Pain relief in conditions such as low back pain and knee osteoarthritis is reported by two studies. [ 28 , 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] However, as the results of the present study suggest, ultrasonographic and electrodiagnostic parameters were significantly changed after treatment only in the CS group. Elawamy et al[ 28 ] demonstrated improved pain, function, neurophysiological, and ultrasonographic improvement six months after receiving O 2 -O 3 injection in systemic sclerosis patients with CTS compared to methylprednisolone. It is worth noting that the dosage of O 2 -O 3 was 25 mu-g/mL in 20 mL, and the procedure was done on a special patient population (i.e., systemic sclerosis patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation